WORKING MEMORY STRUCTURE REVEALED IN ANALYSIS OF RECALL ERRORS - Regina V Ershova; Eugen Tarnow (Peoples' Friendship University of Russia (RUDN University), 2017)
We analyzed working memory errors stemming from 193 Russian college students taking the Tarnow Unchunkable Test utilizing double digit items on a visual display.In three-item trials with at most one error per trial, single incorrect tens and ones digits ("singlets") were overrepresented and made up the majority of errors, indicating a base 10 organization.These errors indicate that there are separate memory maps for each position and that there are pointers that can move primarily within these maps. Several pointers make up a pointer collection. The number of pointer collections possible is the working memory capacity limit. A model for self-organizing maps is constructed in which the organization is created by turning common pointer collections into maps thereby replacing a pointer collection with a single pointer.The factors 5 and 11 were underrepresented in the errors, presumably because base 10 properties beyond positional order were used for error correction, perhaps reflecting the existence of additional maps of integers divisible by 5 and integers divisible by 11.